Case report: An outbreak of viral conjunctivitis among the students and staff of visually impaired school, Tamil Nadu, India, 2020 - Madurapandian, Yazhini; Rubeshkumar, Polani; Raju, Mohankumar; Janane, Aishwarya; Ganeshkumar, Parasuraman; Selvavinayagam, T. S.; Kaur, Prabhdeep (Frontiers in Public Health, 2022)
Introduction On February 2, 2020, the head of a visually impaired school notified similar eye symptoms among the students. We investigated the cluster to confirm the diagnosis, identify potential exposures, and propose recommendations. Methodology We defined a case as redness/watering/discharge from any eye among the students and staff, January–February 2020. We actively searched for the cases and calculated attack rates. We drew epicurve by date of symptoms onset. We conducted a retrospective cohort study of students and staff. We collected data on potential exposures and calculated Risk Ratio (RR), 95% Confidence Interval (95%CI), and Population Attributable Risk (PAR). We sent a conjunctival swab of the three cases for microbiological analysis. Results We diagnosed the cases as acute conjunctivitis and identified 39 (76%) cases among 51 individuals. All the 39 cases reported watering and redness; 28 (72%) and 12 (31%) reported eye pain and discharge, respectively. The median age of the case was 11 years (range: 6–48 years). The attack rate didn't differ significantly between males [77% (20/26)] and females [76% (19/25), p = 0.9]. The attack rate was higher among the students [86%, (38/44)] than staffs [14%, (1/7), p = <0.01]. Contact with a case [RR = 2.5, 95%CI = 1.3–4.8, PAR = 51%] and staying inside campus [RR = 6.0, 95%CI = 1.0–37.3, PAR = 81%] were associated with the acute conjunctivitis outbreak. All the three conjunctival swabs were negative for bacterial growth. Conclusion Close contact with the case and staying inside the campus led to the outbreak of acute conjunctivitis among the students and staff of the visually impaired school.